Analysis of an integrated lens antenna fed by SIW slot array using a hybrid MoM–PO method. Issue 2 (9th December 2015) - Bayderkhani, Reza; Forooraghi, Keyvan; Arnieri, Emilio; Abbasi-Arand, Bijan; Virdee, Bal S.
Abstract : This paper presents a very fast and highly efficient full-wave hybrid method for analyzing an integrated dielectric lens antenna (ILA) fed by multilayered substrate-integrated waveguide (SIW) slot antenna/array. The feeding antenna structure is modeled as a stacked parallel-plate waveguide with metallic posts, coupling, and radiating slots. Physical optics method in conjunction with three-dimensional ray tracing technique is employed to analyze the effect of the dielectric lens on the SIW feeding slots. Fields in the SIW structure are computed by considering the Dyadic Green's function expressed as an expansion of vectorial cylindrical eigenfunctions and taking into account scattering at the conducting posts. Slots are modeled with equivalent magnetic currents expressed as a sum of domain basis functions. By imposing continuity of the tangential components of the fields an integral equation is obtained that is solved with the application of method-of-moments. In order to validate the proposed technique, a hemispherical ILA fed by a double-layered SIW cavity which is backed with slot antenna is analyzed. Excellent agreement is obtained with HFSS software together with significant improvement in computational time and memory requirements.